A review of air pollution impact on subjective well-being: Survey versus visual psychophysics - Li, Yuan; Guan, Dabo; Tao, Shu; Wang, Xuejun; He, Kebin (Journal of cleaner production, 2018)
Air pollution is a worldwide environmental and health issue, especially in major developing countries. A recent World Health Organization report shows about 3 million deaths in the world in 2012 are due to ambient air pollution and China and India are the countries with the most severe challenge. Air pollution influences people's thought and experience of their lives directly by visual perceptions. This reduces people's subjective well-being (SWB) to a significant degree. Empirical researchers have made efforts to examine how self-reported well-being varies with air quality typically by survey method - matching SWB data with monitored air pollution data. Their findings show NO2, particles, lead, SO2 and O3 have significant negative impact on SWB. However, it is very hard to match air pollution characteristics from monitor stations with each respondent's state of SWB at the moment a survey is conducted. Also it is very hard to find the detailed trend impact from only air pollution factor on SWB. This review illustrates the features and limitations of previous survey studies on quantifying the effects of air pollution on subjective well-being. This review further displays the progress of psychophysics and its application in landscape and air quality research. We propose using psychophysics application to quantify air pollution impact on SWB.